(3GdaGUd Hjf GdMb hGdHGWd ef eaGNQ CHfGA bMWGf hGdjefs
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg Hbhdg (B: (3hfTQ ai COHGQ GdCQV hCbUGgG CdhJjc Efi deG SeYJ GdfSGHjf JfGhdJ bhec Hfi bMWGf CfTCJ gPG GdcJGH ai GdeaGNQ hGdCfSGH s
(3BNQgG (B:s
(3LeYJ gPG GdcJGH ef cJH TJi LeYJgG Ydi eSeYjgG hUdi Gddg Ydi SjOfG eMeO NGJe CfHjGFg , hYdi CejQ GdeDefjf Ydi hMSHfG Gddg hfYe Gdhcjd hfYe Gdehdi hfYe GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3efbhdg Yf fSNI ecJhHI SfI (B723 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs